2022
DOI: 10.1177/09612033211072398
|View full text |Cite
|
Sign up to set email alerts
|

Sandplay therapy could be a method to decrease disease activity and psychological stress in children with systemic lupus erythematosus

Abstract: Objective Although the prevalence rate of childhood-onset systemic lupus erythematosus (cSLE) is far lower than that of adults, cSLE has a high rate of organ involvement, rapid development and poor prognosis, which is more serious than that in adults. And studies have shown that a wide range of physiological, functional, nerve, and organ damage will have a great impact on the mental health of children. At present, there is no relevant psychological intervention research for cSLE in China. This paper aimed to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…③ Objective information reference: in conventional therapy, the child has a psychological barrier, and it is difficult for the practitioner to read the child's inner world from just a few words while using the work as an objective information reference; through the work, the therapist can clearly observe the child's inner world. Then, according to the cognitive-behavioural theory of psychology, the therapist provides targeted guidance to help the child find strength in self-growth and promote deep personality integration, which helps the child's emotional and mental stability and behavioural and cognitive improvement after treatment [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…③ Objective information reference: in conventional therapy, the child has a psychological barrier, and it is difficult for the practitioner to read the child's inner world from just a few words while using the work as an objective information reference; through the work, the therapist can clearly observe the child's inner world. Then, according to the cognitive-behavioural theory of psychology, the therapist provides targeted guidance to help the child find strength in self-growth and promote deep personality integration, which helps the child's emotional and mental stability and behavioural and cognitive improvement after treatment [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…en, according to the cognitivebehavioural theory of psychology, the therapist provides targeted guidance to help the child nd strength in selfgrowth and promote deep personality integration, which helps the child's emotional and mental stability and behavioural and cognitive improvement after treatment [20].…”
Section: Discussionmentioning
confidence: 99%
“…In a study that affected the reduction of depressive symptoms after SGT intervention, Li et al [ 39 ] reported significant decreases in anxiety and depression in children with systemic lupus erythematosus after SGT. Keivani et al [ 40 ] SGT alleviated depressive symptoms in preschoolers.…”
Section: Discussionmentioning
confidence: 99%
“…Tan et al [38] observed the effect of sandplay therapy in alleviating anxiety and social problem behaviors in school-aged children with chronic diseases. In a study that affected the reduction of depressive symptoms after SGT intervention, Li et al [39] reported significant decreases in anxiety and depression in children with systemic lupus erythematosus after SGT. Keivani et al [40] SGT alleviated depressive symptoms in preschoolers.…”
Section: Discussionmentioning
confidence: 99%
“…Psychosocial stress in all age groups irrespective of gender serves as a great risk factor for poor outcomes from SLE [ 28 ]. A recent study revealed stress as the strongest poor prognostic indicator of poorly controlled SLE [ 29 ]. Psychosocial stress single-handedly leads to a poor prognosis with flares of high intensity in activities of daily life [ 30 ].…”
Section: Discussionmentioning
confidence: 99%